2014
DOI: 10.3810/pgm.2014.09.2812
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparison of 600 mg versus 300 mg Loading dose of Clopidogrel for Patients with ST-Elevation Myocardial Infarction: A Meta-Analysis

Abstract: In ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention, administration of a 600-mg LD of clopidogrel is associated with a lower risk of MACE than is administration of a 300-mg LD, without increasing the risk of major bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This is most likely caused by pharmacological interventions of the patients. In accordance, it has previously been shown that pre-hospital medication with 300 mg aspirin caused a 50% reduction in platelet aggregation using AA stimulation whereas anti-platelet effect of clopidogrel was observed after 72 h [28]. The rapid effect of aspirin is expected based on the known pharmacokinetics of aspirin and the ISIS-2 study published three decades ago that showed a beneficial effect of platelet inhibition [29,30].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This is most likely caused by pharmacological interventions of the patients. In accordance, it has previously been shown that pre-hospital medication with 300 mg aspirin caused a 50% reduction in platelet aggregation using AA stimulation whereas anti-platelet effect of clopidogrel was observed after 72 h [28]. The rapid effect of aspirin is expected based on the known pharmacokinetics of aspirin and the ISIS-2 study published three decades ago that showed a beneficial effect of platelet inhibition [29,30].…”
Section: Discussionmentioning
confidence: 59%
“…This may explain the modest effect on platelets stimulated by ADP. In comparison, other studies have shown that a higher loading dose (600 mg) induces a more rapid and significantly better effect of the drug [28]. The time from medication with clopidogrel to the arrival at the catherization laboratory was approximately 80 min.…”
Section: Discussionmentioning
confidence: 78%
“…Several recent cardiology trials suggest that a loading dose of 600 mg might be more effective in preventing major adverse cardiac events, without increasing the risk of bleeding. 15 However, for PAOD patients there is no evidence that suggests superiority of a higher loading dose.…”
Section: Post-procedural Antiplatelet Therapymentioning
confidence: 99%